Influence of Intensity of Rain Strains and Slopes on the Development of Soil Erosion under the Forest - Mustafin, Radik F.; Sultanova, Rida R.; Khasanova, Luiza M.; Rajanova, Anzhelika R.; Khazipova, Aigul F. (Journal of Environmental Accounting and Management, 2026)
The purpose of this study is to determine the degree of influence of rain intensity on the soil of the tested slopes of the regional forestry. The paper analyzes the results of studies conducted in the Birsk forestry in the water protection zone. The results of studies of the water permeability of the steep and hollow slopes of the forest massif are presented. After the runoff beginning and with its increase by 1 mm, the mass of washed soil on slopes with the steepness of 15 $^°$/ 30 $^°$ reaches 6.2/23.7 t/ha on cultivated lands.